Proposed Actions For The Completion of PLTU Lampung/Tarahan Baru Project Effectively - Sistarani, Meutia; Bekti, Rudy (The Indonesian Journal of Business Administration, 2012)
PLTU Lampung/Tarahan Baru is one of the projects that was included in this 10.000 MW mega project and is planned to distribute electricity with the capacity of 2 x 100 MW. The evaluation results of PLTU Lampung/Tarahan Baru indicate a delay in the project completion time for at least 20 months from the original plan. Using the fishbone diagram, it was found that the loans problems, employee payroll, material delivery schedules, permits, engineering drawings, and contractors who do not work well is the cause of the delay in completion of this project. An analysis using Analytical Hierarchy Process (AHP) produces three main priorities to be done which are to extend the loan, to update the material distribution licenses, and to give penalties to the contractors that late in paying their employees. Sixteen proposed actions were analyzed using the 7S McKinsey framework and then being implemented using the PDCA (Plan Do Check Act) format. Keywords: Pembangkit Listrik Tenaga Uap (PLTU), project management, Analytical Hierarchy Process (AHP), 7S McKinsey, Plan Do Check Act (PDCA)